2000
DOI: 10.1054/bjoc.1999.0986
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviour, STDs and risks for prostate cancer

Abstract: A population-based case-control study was carried out among 981 men (479 black, 502 white) with pathologically confirmed prostate cancer and 1315 controls (594 black, 721 white). In-person interviews elicited information on sexual behaviour and other potential risk factors for prostate cancer. Blood was drawn for serologic studies in a subset of the cases (n = 276) and controls (n = 295). Prostate cancer risk was increased among men who reported a history of gonorrhoea or syphilis (odds ratio (OR) = 1.6; 95% c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
118
5
8

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(146 citation statements)
references
References 42 publications
14
118
5
8
Order By: Relevance
“…To our knowledge, no nationally representative estimates of the cumulative incidence of gonorrhea exist. Our null finding for gonorrhea is consistent with the results from eight previous case-control studies (12)(13)(14)(15)(16)(17)(18)(19) but differs from those from an additional six case-control studies and meta-analysis findings (2,7,11,(20)(21)(22)(23). Profound nondifferential misclassification of gonorrhea due to poor recall or a reluctance to report stigmatizing diseases is unlikely to explain our null result for several reasons.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…To our knowledge, no nationally representative estimates of the cumulative incidence of gonorrhea exist. Our null finding for gonorrhea is consistent with the results from eight previous case-control studies (12)(13)(14)(15)(16)(17)(18)(19) but differs from those from an additional six case-control studies and meta-analysis findings (2,7,11,(20)(21)(22)(23). Profound nondifferential misclassification of gonorrhea due to poor recall or a reluctance to report stigmatizing diseases is unlikely to explain our null result for several reasons.…”
Section: Discussionsupporting
confidence: 80%
“…For instance, among men born earlier in calendar time, a history of gonorrhea may be more likely to reflect a longer duration of non -antibiotic-treated infection, which frequently resulted in prostatitis (25). As a further example, among men of different race/ethnicity, socioeconomic, or educational status, a history of gonorrhea may be more likely to represent multiple episodes of gonorrhea (or possibly coinfections), which were more strongly associated with prostate cancer than single episodes of gonorrhea in a case-control study by Hayes et al (11). Therefore, although our null study findings are likely generalizable to most men in developed countries who are unlikely to experience more than a few episodes of treated gonorrhea, we cannot rule out possible associations between repeated episodes of gonorrhea (or coinfections) and prostate cancer and between untreated or delayed-treated gonorrhea and prostate cancer in populations with a higher burden of STIs.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to a meta-analysis that reported significantly elevated pooled odds ratios for gonorrhea and syphilis [23]. Hayes et al [24] reported elevated risks of prostate cancer associated with a history of gonorrhea or syphilis that were similar for African-American and Caucasian men. Although the percentage of Caucasian men in our study reporting a history of STI was comparable to that reported by Hayes et al, the percentage of African-American men was lower indicating there may have been underreporting of this sensitive topic.…”
Section: Discussioncontrasting
confidence: 74%
“…52 Finally, an association between sexually transmitted infections and risk of prostate cancer has been reported53; although results of testing for sexually transmitted infections are not available in administrative data, we also evaluated the number of these tests performed during the study period.…”
Section: Methodsmentioning
confidence: 99%